1990
DOI: 10.1002/sia.740150808
|View full text |Cite
|
Sign up to set email alerts
|

Sputter reduction of oxides by ion bombardment during Auger depth profile analysis

Abstract: Quantification of the magnitude of preferential sputtering of oxygen from metallic oxides has been examined for a large number of 30 nm thick amorphous oxides deposited onto polished silicon substrates. The method of analysis was derivative-mode Auger analysis carried out in a cleaner vacuum system and with cleaner initial surfaces than has been the case usually for data found in the literature. Ion sputtering was primarily with 3 keV xenon ions but the effect of ion energy (1, 3 and 4.5 keV), ion mass (argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 25 publications
(4 reference statements)
5
68
0
Order By: Relevance
“…Our suspicion is based on our observations as well as those of others that severe oxygen-de cient stoichiometry results during noble gas ion bombardment of metal oxides containing similar metal ions. 5,[11][12][13][14][15] It is interesting that the electrochemical reduction potentials determined in aqueous solutions can also be the determining factors for the stability of the ions on various surfaces and/or towards energetic particle bombardment. To this end one m ust also consider that, during energetic particle bombardment, copious amounts of secondary low-energy electrons are produced, which must be inducing reactions similar to the ones in the aqueous phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our suspicion is based on our observations as well as those of others that severe oxygen-de cient stoichiometry results during noble gas ion bombardment of metal oxides containing similar metal ions. 5,[11][12][13][14][15] It is interesting that the electrochemical reduction potentials determined in aqueous solutions can also be the determining factors for the stability of the ions on various surfaces and/or towards energetic particle bombardment. To this end one m ust also consider that, during energetic particle bombardment, copious amounts of secondary low-energy electrons are produced, which must be inducing reactions similar to the ones in the aqueous phase.…”
Section: Resultsmentioning
confidence: 99%
“…2-10 Electron, ion, and other energetic particle exposure, which is frequently utilized for cleaning and/or depth-pro ling, also causes damage, and similar to Xrays, this approach invariably gives rise to the reduction of the m etal ions to lower oxidation states and/or preferential removal of oxygen. 5,[11][12][13][14][15] The extent of reduction, however, varies drastically from one metal ion to another.In this contribution, we will demonstrate reduction by X-rays of Au, Hg, Bi, V, and W m etal ions during our XPS analysis of various kinds of samples we have carried out over the years. 16,17 We will also discuss the possibility of correlating the ability of the metal ions to undergo Xray-induced reduction with their electrochemical reduction potentials.…”
mentioning
confidence: 99%
“…In addition to X-rays, electron, ion, and other energetic particle exposures, which are frequently encountered for cleaning and/or depthprofiling, also cause reduction of certain metal ions to their lower oxidation states [29][30][31][32][33][34]. The extent of reduction varies drastically from one metal ion to another and extensive efforts had been devoted to correlate this with certain chemical/ physical properties of them [24][25][26][27][28][29][30][31][32][33][34]. In one of our earlier work, we had claimed that the extent of X-ray induced reduction could be related with the electrochemical reduction potential of the metal ion [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…There is a long history (e.g., [6]) of studies concerning the explanation of the bombardment-induced surface compositional changes in oxides ( [11], [12], [13], [14] and [15]). In all these studies it was found that if there are any surface compositional changes, then oxygen was preferentially lost from the oxide surface.…”
Section: Introductionmentioning
confidence: 99%